Amended description and a new synonym for Henckelia hookeri (Gesneriaceae) with notes on its typification - Maity, R.; Chowlu , K.; Dash, S. S. (Rheedea, 2025)
The recently described species, Henckelia arupii Taram & Tag (Gesneriaceae) is found to be conspecific to H. hookeri (C.B.Clarke) D.J.Middleton & Mich.Möller. Therefore, the former name has been reduced here as a heterotypic synonym under the latter based on the morphological studies. Additionally, description for this taxon has been amended to resolve ambiguities and its easy identification. Additional notes on the lectotypification of the name Chirita hookeri C.B.Clarke, the basionym for H. hookeri is also provided.